2017
DOI: 10.1111/acel.12665
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin deposition promotes progression of osteoarthritis

Abstract: SummaryDeposition of amyloid is a common aging‐associated phenomenon in several aging‐related diseases. Osteoarthritis (OA) is the most prevalent joint disease, and aging is its major risk factor. Transthyretin (TTR) is an amyloidogenic protein that is deposited in aging and OA‐affected human cartilage and promotes inflammatory and catabolic responses in cultured chondrocytes. Here, we investigated the role of TTR in vivo using transgenic mice overexpressing wild‐type human TTR (hTTR‐TG). Although TTR protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…To our knowledge, concentrations of IL10, IL6 and IFNG have not been reported in SF from OA CMC-I joints. Furthermore, IL6, IL10 and IFNG molecules are involved in similar molecular pathways as CCR6, TTR, CLU and PON1 [23,29,35,36]. In this work, an inverse relationship encompassing anti-inflammatory molecule, IL10 with CLU and PON1 was observed.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, concentrations of IL10, IL6 and IFNG have not been reported in SF from OA CMC-I joints. Furthermore, IL6, IL10 and IFNG molecules are involved in similar molecular pathways as CCR6, TTR, CLU and PON1 [23,29,35,36]. In this work, an inverse relationship encompassing anti-inflammatory molecule, IL10 with CLU and PON1 was observed.…”
Section: Discussionsupporting
confidence: 62%
“…2). TTR has previously been implicated in OA pathogenesis, inflammatory responses and in inflammatory diseases such as RA and gout [23,24] [23]. CCR6 and its ligand CCL20 are known to be upregulated in OA cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…In the study on osteoarthritis by Rubin et al [44], no examination of the joint tissue was performed, but it was hypothesized that amyloid deposition could be directly pathogenic. This hypothesis was supported by a mouse model of osteoarthritis, where it was shown that the overexpression of TTR worsened the progression of the disease [45]. Taken together, the three studies indicate that ATTRwt amyloidosis is not only a cardiac disease.…”
Section: Discussionmentioning
confidence: 76%
“…As previously reported, TTR deposition in human OA cartilage was observed and exerted cytotoxicity for human chondrocytes [15]. Very recently, Matsuzaki et al have reported an intriguing mechanism by which TTR deposition promotes OA in murine models [32]. TTR deposition was found in the synovium of aged mice and enhanced inflammatory gene expression, resulting in OA progression.…”
Section: Effect Of Gpc On Oamentioning
confidence: 71%